Fabrication of a Novel PES/CNTs@TiO2 Membrane Combining Photo-Electrocatalysis and Filtration for Organic Pollutant Removal - Yue Lu; Xuan Xing; Yi Jiang; Jianxin Xia (Membranes)
Membrane filtration has been widely used in wastewater treatment; contaminants attached to the membrane surface led to flux loss and service life reduction. In the present study, a photo-electrocatalysis membrane was fabricated with CNTs@TiO2 deposited on a commercial polyethersulfone (PES) membrane (PES/CNTs@TiO2). XRD and SEM characterization proved that the CNTs@TiO2 composites were successfully fabricated using the one-pot hydrothermal method. Additionally, vacuum filtration was used to distribute the as-prepared powder on the PES membrane. In CNTs@TiO2, TiO2 particles were deposited on the outer layer of CNTs, which benefits light adsorption and photocatalytic reaction. The hydrophilicity, light absorption ability, and electron transfer rate of the PES/CNTs@TiO2 membrane were enhanced compared with the pristine PES membranes. Organic compound removal was improved in the photo-electrocatalysis filtration system with the improvement of 32.41% for methyl orange (MO), 26.24% for methyl blue (MB), 7.86% for sulfamethoxazole (SMZ), and 25.19% for florfenicol (FF), respectively. Moreover, the hydrophilicity and removal rate could be restored after pure water cleaning, demonstrating excellent reusability. The quenching experiment showed that ·OH and ·O2− were the main reactive oxygen species. This work provides a convenient form of photo-electrocatalysis filtration technology using modified commercial membranes, which has great potential for practical application.